(untitled) (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
This article explores several case studies of key monastic foundations in both Eastern and Western Christianity in order to underline the symbolic significance of landscapes, such as deserts, gardens, and rivers, within monastic literature. The rhetoric surrounding these spaces often idealized isolation and spiritual retreat while simultaneously acknowledging the social and physical proximity of monasteries to urban centers and significant commercial routes.